Design and validity of interactive multimedia based on cognitive conflict in kinetic gas theory materials using adobe animate cc - Nadya Sari Putri; Fatni Mufit; Amalia Putra; Hidayati Hidayati (Universitas Sultan Ageng Tirtayasa, 2023)
The 21st century learning requires students to have 4C skills in addition to understanding students' concepts. However, students' 4C skills and understanding of concepts in physics are still relatively low and there are still many misconceptions and the unavailability of teaching materials that can improve students' 4C abilities and conceptual understanding. This study aims to create a valid cognitive conflict-based interactive multimedia design to improve students' 4C skills and understanding of the concept of gas kinetic theory. This type of research is a development/design research using the Plomp model and this research is limited to the prototyping stage. At the preliminary research stage, it was found that in the range of 25% - 43% of students experienced misconceptions ,and in the range of 18% - 55% of students didn,t understand the concept.. In the development and prototyping stages of designing interactive multimedia, the interactive multimedia designs that have been made are carried out with self evaluation has been carried out with a very valid result of 0.96 and an expert review with a very valid result of 0.82. the result shown the conflict-based interactive multimedia can be used to improve student understanding of 4C abilities and conceptual understanding.